How to Measure and Increase Second Language Writing Motivation - Eryılmaz, Ali; Yesilyurt, Yusuf Emre (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This study aimed to develop a Second Language (L2) Writing Motivation Scale in an EFL context. Within this central aim, sub-studies in three phases were carried out: 1) to create an L2 Writing Motivation Scale, 2) to perform a confirmatory factor analysis and validate the scale, and 3) to test two path models regarding increasing students’ intrinsic motivation and decreasing their amotivation towards L2 writing. The participants included a total of 657 students from different departments of three large state universities. In the first of three study phases, an L2 Writing Motivation Scale was developed. Then, exploratory factor analysis was conducted, and a three-dimension L2 writing motivation scale emerged. Here, the test-retest reliability coefficient of the scale’s dimensions was found to be satisfactory. In the second phase, confirmatory factor analysis was performed, and the scale construction was validated. Finally, two path models regarding increasing students’ intrinsic motivation and decreasing their amotivation towards L2 writing were found to fit perfectly. The possible contribution of the use of the scale in L2 writing pedagogy is discussed.